Exploring the bulk-phase structure of ionic liquid mixtures using small-angle neutron scattering. (26th September 2017) - Cabry, Christopher P.; D'Andrea, Lucía; Shimizu, Karina; Grillo, Isabelle; Li, Peixun; Rogers, Sarah; Bruce, Duncan W.; Canongia Lopes, José N.; Slattery, John M.
Abstract : Small-angle neutron scattering experiments, supported by molecular dynamics simulations, have been performed on a range of compositions of the [C2 mim]1− x [C12 mim] x [Tf2 N] ionic liquid mixture system. Abstract : Small-angle neutron scattering experiments, supported by molecular dynamics simulations, have been performed on a range of compositions of the [C2 mim]1− x [C12 mim] x [Tf2 N] ionic liquid mixture system. Isotopic contrast variation, through selective deuteration of both cations, has been used to assist in fitting the data to different scattering models. These data, and subsequent fitting, show that the structure of the ionic liquid mixtures changes substantially as a function of composition. Mixtures where x < 0.32 are dominated by aggregates of amphiphilic [C12 mim] + ions in the relatively polar [C2 mim][Tf2 N] solvent. Compositions where x > 0.32 can be described as bicontinuous, containing networks of both polar and non-polar domains, where the C12 chains of the [C12 mim] + ions percolate through the system to form a continuous non-polar sub-phase. Temperature-dependent scattering experiments suggest that there is relatively little change in bulk structure in these liquids between 20 and 60 °C. The presence of water, however, does influence some aspects of the liquid structure in a composition that is rich in [C2 mim][Tf2 N] (where x = 0.24).